BRAF inhibitors in BRAF-V600 mutated primary neuroepithelial brain tumors. (2nd January 2016) - Preusser, Matthias; Bienkowski, Michal; Birner, Peter
Abstract : Introduction : Primary neuroepithelial brain tumors encompass a wide variety of glial and glioneuronal neoplasms. Malignant tumors, tumors located in surgically inaccessible locations (e.g., eloquent brain areas, deep structures, brain stem) and recurrent or progressive tumors pose considerable treatment challenges and are candidates for novel therapeutics based on molecular insights. Small kinase inhibitors of v-RAF murine sarcoma viral oncogene homologue B1 (BRAF) have shown considerable antineoplastic activity in some tumor types harboring activating BRAF-V600 mutations (e.g., melanoma) and promising data are emerging on BRAF inhibitor therapy of mutation-bearing primary brain tumors. Areas covered : This review summarizes the available data on BRAF-V600 point mutations and the antineoplastic activity and toxicity profiles of BRAF inhibitors in neuroepithelial brain tumors including diffuse gliomas (glioblastomas, astrocytomas, oligodendrogliomas), pilocytic astrocytomas, pleomorphic xanthoastrocytomas and gangliogliomas. Expert opinion : Activating BRAF-V600 mutations are recurrently found in several glial and glioneuronal brain tumors and the available data indicate that BRAF inhibitors are active and well-tolerated in such tumors. Thus, BRAF inhibitors represent a novel and promising therapeutic opportunity that may alter the disease course of molecularly selected CNS neoplasms in a clinically meaningful way. However, so far the evidence is anecdotal and prospective clinical studies should be conducted.